THE EFFECT OF STANDARD MARINE COMMUNICATION PHRASES APPLICATION THROUGH ENGLISH FOR MARITIME ABILITY - Diah Paramita Sari; Aprizawati Aprizawati (Politeknik Negeri Bengkalis, 2019)
Abstractâ€”This research was conducted to investigate the significant differences of SMCP Application throughÂ English for Maritime ability students. By conducting quasi experimental research, the write tries to know whether SMCP Application is effective in helping maritime students in learning English for maritime. This research was quasi experimental research. The sample was taken by purposive sampling. There were 27 students from Nautical Study program and 26 students from Port and Management study program. The data of this research were the results of studentsâ€™ English test. After conducting pre-test and post-test, the average of gained score was 17.66. The students who taught by SMCP Application have higher score in post-test than pre-test. Since t-observed = 8.33 was higher than t-table = 1.645, it means that Ha was accepted. The result of this research was students who are taught by SMCP have better English ability than those who are taught by conventional teaching. In conclusion, SMCP can be used as a teaching technique in teaching English for Maritime.